Urban Development for the 21st Century 2015
DOI: 10.1201/b18765-7
|View full text |Cite
|
Sign up to set email alerts
|

How Urban Societies Can Adapt To Resource Shortage And Climate Change

Abstract: Like most cities in developing countries, Kigali is experiencing rapid urbanisation leading to an increase in the urban population and rapid growth in the size and number of informal settlements. More than 60% of the city's population resides in these settlements, where they experience inadequate and poor quality urban services including sanitation. This article discusses the issues and constraints related to the provision of sustainable sanitation in the informal settlements in Kigali. Two informal settlement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…However, unlike other developing cities such as Kampala, Nairobi and Dar-es-Salaam, Kigali has no clear strategy for the emptying of pit latrines [1,15] and only 2% of households empty sludge from their pits. Therefore, there is a risk of the full latrine overflowing, contaminating the environment with large quantities of excreta containing harmful pathogens and causing offensive smells [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike other developing cities such as Kampala, Nairobi and Dar-es-Salaam, Kigali has no clear strategy for the emptying of pit latrines [1,15] and only 2% of households empty sludge from their pits. Therefore, there is a risk of the full latrine overflowing, contaminating the environment with large quantities of excreta containing harmful pathogens and causing offensive smells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thaxton ( 2009 ) as well as Lubaale and Musyoki ( 2011 ) observed that dwellers of urban informal neighbourhood usually used unimproved water sources and unsanitary latrine facilities. Drainage and waste management systems were inadequate or nonexistent in some places (Hohne, 2011 ; Karangwa, 2009 ; Tsinda and Abbott, 2012 ). Although the situation is quite similar to other urban informal settlements of developing countries, we assumed that the mountainous nature of the physical environment in Rwanda (REMA, 2010 ) coupled with poor drainage systems and inadequate waste management may compound the prevalence of diarrhoea and introduce diarrhoea risk variations among dwellers of the same neighbourhood.…”
Section: Introductionmentioning
confidence: 99%
“…With reference to the cost involved to acquire a type of toilet, we devised three categories: traditional pit, fairly improved and modern toilet facilities. According to Sano in Tsinda and Abbott ( 2012 ), the construction of a modern toilet facility in Kigali requires 1,500 to 3,000 US dollars while a traditional pit toilet facility can range from 180 to 350 US dollars or less. The cost for each toilet type is based on its quality as was observed: while modern toilet facilities typically satisfy WHO, and UNICEF ( 2006 ) standards (flush toilets, or cemented facilities with the pit covered and water connections which allow for a specific place for hand-washing), traditional pit toilet facilities were usually not cemented; instead, they were covered by timber, and doors were unlocked to allow sharing among different neighbouring households whenever needed.…”
Section: Introductionmentioning
confidence: 99%
“…In settlements like those of Kisumu, they collapse during rainy seasons due to the weak soil structure and high water table, they attract flies and the pits can be breeding grounds for insects such as mosquitoes which pose public health risks and are a nuisance to users (Nakagiri et al 2016). In addition, they often need to be emptied when they fill up which is a challenge in slums because municipal trucks cannot access the congested slums (Katukiza et al 2012;Tsinda et al 2013;Kwiringira et al 2014;Semiyaga et al 2015).…”
Section: Discussionmentioning
confidence: 99%